Kurd and philosophy: looking at the relationship between philosophy and literature according to Aladdin Sajadi - Abdollah Amini (پژوهشنامه ادبیات کردی)
AlaAddin Sajadi in History of Kurdish Literature, has tried to lay a foundation for researchers in Kurdish literature, and narrates the experiences of the Kurdish “volksgeist”. In the section “Kurd and Philosophy”, Sajadi briefly presents issues about philosophy, relationship between philosophy and literature, the beginning of philosophy as well as “Kurdish philosophy”, which is worthy of reflection. Due to the fact that this text is apparently the first approach of a Kurdish writer in the Kurdish language about philosophy, we considered it worthy of analysis and investigation. In this paper, relying on the phenomenological-hermeneutic method, the author has tried to show the context of Sajadiʹs thought as well as his view in relation to literature and philosophy, and has tried to reread the mentioned section in the framework of Sajadiʹs “Cultural Project”. In addition, relying on hermeneutic approach, the author has tried to highlight two different meanings of the concept of beginning in Sajadiʹs text, and possibility of the beginning of philosophy in Kurdish rationality. The main question of the paper is what exactly Sajadiʹs approach of philosophy and literature is, that in a book about the history of literature, he finds himself compelled to discuss philosophy and “Kurdish philosophy”?